Perampasan ASET Dalam Perbankan Atas ASET Yang Dihasilkan Melalui Tindak Pidana Pencucian Uang Dan Akibat Hukum Atas Hubungan Hukum Antara Perbankan Dengan Nasabah Penyimpan Atas ASET Yang Dirampas - Ahmad Shobari; Anzira Sania Desivha ; Mita Riza Rahmanda ; Reza Dio Wijatmika ; Nabiella Putri Nastiti (Universitas Sains dan Teknologi Komputer, 2024)
This research aims to provide insight and knowledge for readers regarding Asset Forfeiture in banking on assets generated through Money Laundering Crimes and legal consequences on a legal relationship between banks and depositors on assets that are seized. The background in this research concerns the conception of Indonesia as a state of law in carrying out its role as a state through state representatives who have law enforcement status in carrying out the law enforcement process in money laundering cases, especially in carrying out a series of mechanisms to seize the assets of suspects or defendants in banking. The research method in this study uses normative research methods by analyzing the identification of problems outlined in this discussion with various laws and regulations related to this discussion and strengthened by literature data consisting of books and legal research journals. In the research in the first sub-chapter discussion analyzes and discusses asset forfeiture in banking for assets resulting from money laundering crimes by linking to the relevant laws and providing an explanation of the formal law in conducting asset forfeiture in banking. Then, in the second sub-chapter discussion discusses and analyzes the legal consequences of the legal relationship between banks and depositors on assets that are seized and indicated that the assets are generated through money laundering for the benefit of cases in the criminal justice process.